Starch industry development as a strategy for agro-food based rural industrialization - Goletti, Francesco; Rich, Karl M.; Wheatley, Christopher; Nguyen, Kim Vu (International Food Policy Research Institute, 1998)
To promote development, there is increasing need for activities and policies which generate and diversify income in rural areas. The starch industry in Viet Nam provides a good example of rural industrialization whereby low-value agricultural commodities such as cassava and canna are processed into high-value commodities such as starch to be used in a variety of food and non-food industries. Though this sector is relatively small, it has a high potential in terms of demand growth, poverty reduction, and income diversification in rural areas, particularly the less favored ones. The project had five main objectives: 1) to characterize the production and consumption of starch in Viet Nam; 2) to describe the marketing channels for the starch distribution system; 3) to identify the key policy issues related to the promotion of the starch industry as a strategy for rural industrialization; 4) to analyze the effects of alternative policy options for accelerating growth of the starch industry; and 5) to identify priorities for further research. The study found that growth in the starch industry has been dramatic. Over the past 10 years, the share of cassava used to process starch has grown about 250 percent, while average investment has increased by 78 percent each year. Most participants are new entrants (62 percent have entered since 1988), while industrial capacity has grown 8-fold between 1994 and 1997 alone. Moreover, the industry has strong linkages with rural development as many rural households become involved in processing through small enterprises. Rural households working as starch processors make more than twice the income of the average rural household. In turn, the industry drives increased cassava production. However, the industry faces several constraints to greater productivity: low levels of technology adoption by small operators who comprise the majority of producers; limited access to credit; the high cost of raw materials; and environmental degradation, as starch residue pollutes local water supplies. Based on an econometric analysis of key policy alternatives, the following policies were judged the most sound: research and extension activities to increase raw material (e.g. cassava) yield at the farm level, and to raise the quality of starch to compete internationally through appropriate institutions; and an increase in credit access for capital equipment investment, particularly among small and medium scale enterprises. Post-Production Research Network of International Development Research Center (IDRC), December 1998.; Donor report submitted to the International Development Research Center. December 1998